2022
DOI: 10.1111/socf.12819
|View full text |Cite
|
Sign up to set email alerts
|

“It's (Not) Like the Flu”: Expert Narratives and the COVID‐19 Pandemic in Mainland China, Hong Kong, and the United States

Abstract: We trace the crafting of expert narratives during the initial months of the COVID-19 pandemic in Mainland China, Hong Kong, and the United States. By expert narratives, we refer to how experts drew different lessons from past disease experiences in order to guide policymakers and the public amidst uncertainty. These expert narratives were mobilized in different sociopolitical contexts, resulting in varying configurations of expertise networks and allies that helped contain and mitigate COVID-19. In Mainland Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…They are then ‘more successful in predicting the future’ than the expert, ‘who knows one big thing, toils devotedly within one tradition, and imposes formulaic solutions on ill‐defined problems’ (Tetlock, 2017). Experts are designed to recognize similarities between the present moment and past experiences (Au et al, 2022). When confronted with a new crisis, experts encounter realms of knowledge that are unexplored and fresh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are then ‘more successful in predicting the future’ than the expert, ‘who knows one big thing, toils devotedly within one tradition, and imposes formulaic solutions on ill‐defined problems’ (Tetlock, 2017). Experts are designed to recognize similarities between the present moment and past experiences (Au et al, 2022). When confronted with a new crisis, experts encounter realms of knowledge that are unexplored and fresh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a first approximation, the paucity of Long Covid patients is explicable in relation to how the pandemic unfolded in China. Initially, Covid-19 was quickly read against the experience in 2003 with the outbreak of SARS (Au, Fu, and Liu 2022), and Chinese experts recognized the potential catastrophe. This resulted in the lockdown of Wuhan and other cities (Yang 2022), followed by the implementation of the !health code" system that purported to help trace potential exposures and limit the spread of Covid-19 (Liu 2022;Liu and Graham 2021).…”
Section: The Stigma Of Long Covidmentioning
confidence: 99%
“…Initially, Covid-19 was quickly read against the experience in 2003 with the outbreak of SARS (Au, Fu, and Liu 2022), and Chinese experts recognized the potential catastrophe. This resulted in the lockdown of Wuhan and other cities (Yang 2022), followed by the implementation of the !health code" system that purported to help trace potential exposures and limit the spread of Covid-19 (Liu 2022;Liu and Graham 2021). These measures by the Chinese government had the effect of keeping the numbers of Covid-19 infections relatively low, which is why they were referred to as the "Zero Covid" policy.…”
Section: The Stigma Of Long Covidmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found differences in why residents of the U.S. versus Singapore supported travel bans (Moran et al., 2021), suggesting disparities in risk assessment and how public health influences individuals. However, while xenophobia and racism have historic associations with pandemics (Moran et al., 2021; White, 2023) and some news outlets warned of this during the early COVID outbreak (e.g., Au et al., 2022), xenophobia may be a weaker predictor of travel ban support relative to proximity an outbreak (Moran et al., 2021). Regarding early public coronavirus messaging, countries responded in a way that reflected their response to the SARS outbreak of 2003, with China attempting to repress information, Hong Kong attempting to face outbreaks head‐on and combat repression, and the U.S. expressing skepticism and lack of clarity (Au et al., 2022).…”
Section: Targeting Specific Diseases On a Global Scalementioning
confidence: 99%